FIQH KEINDONESIAAN: Transformasi Hukum Islam Dalam Sistem Tata Hukum Di Indonesia - Tohari, Chamim (Universitas Islam Negeri Raden Intan Lampung, 2015)
INDONESIAN JURISPRUDENCE: ISLAMIC LAW TRANSFORMATION IN LAW SYSTEM OF INDONESIA.: This study discusses about the idea of Islamic law renewal in Indonesia, as well as the figures, and it makes the term of Indonesian Jurisprudence and its formalization into the law system of Indonesia. The purpose of this study is to find the answer of these following points: Firstly, the interpretation or definition of Indonesian Jurisprudence concept; secondly, the figures who proposed Indonesian Jurisprudence and the result of their thoughts; and the third, the formalization of Jurisprudence concept with Indonesian nuance in the law system Indonesia. This study was a library research with a content analysis method. The results of this study are: (1) Indonesian Jurisprudence could be interpreted as a Jurisprudence concept that is more Indonesian local-based; (2) Hasbi As-Shiddiqi and Hazairin are two figures who proposed Indonesian Jurisprudence model, apart from other intellectuals. Hasbi is one of modernists who offered his ideas comprehensively, started from his “Indonesian Jurisprudence” concept until the law renewal including its principle and method. Meanwhile Hazairin offered the development of a new heritage system which interpreted and elaborated based on Al-Qur’an scriptural perception and Sunnah which is not a patrilineal system but bilateral family model); and (3) formalization of Indonesian Jurisprudence concept produces some ordinance regulation products which are important formally and materially, such as Ordinance of Islamic Marriage Law, and also other rules under the Ordinance, such as Government Law, President Instruction, and Supreme Court Law, as well as Islamic Law Compilation and Sharia Economic Law Compilation